Analisis Yuridis Penyelesaian Kepailitan dalam Perspektif Hukum Acara Perdata Terhadap Tanggung Jawab Debitur dan Pihak Ketiga - Pangesti, Indri; Eka Febriantika, Nur Afifah; Lainatusyifa, Ahida; Kurniawati , Titis (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This article examines the resolution of bankruptcy from the perspective of civil procedural law, with an emphasis on the responsibilities of debtors and third parties. Bankruptcy in Indonesia is governed by Law No. 37 of 2004 on Bankruptcy and Suspension of Debt Payment Obligations (UUK-PKPU), while the Civil Code (KUHPerdata) continues to provide a general legal framework related to contracts and civil liabilities. The bankruptcy process begins with a petition to the District Court, followed by case examination, bankruptcy ruling, appointment of a receiver, and liquidation of the debtor's assets. A case study of PT Dirgantara Indonesia in 2007 is used to illustrate the practical challenges and processes involved in bankruptcy resolution. The findings indicate that while the Bankruptcy Law provides specific rules, the principles of the Civil Code remain relevant in determining responsibilities and creditor rights. The article suggests the need for stronger debt restructuring policies and effective prevention measures to reduce future bankruptcy risks and ensure a fair and sustainable debt resolution process.